The public servant’s role in democracy - Boyd, Brendan; Westley, Jared J.; Rounce, Andrea; Levasseur, Karine; Caron, Isabelle (My University, 2021)
This research note reports on the findings from a survey conducted in partnership with the Institute of Public Administration of Canada (IPAC). Despite robust debate among public administration experts about the role public servants should play in Canadian democracy, there has yet to be a systematic study of how public servants themselves view democracy and their role within it. We ask: What role do public servants play in democracy? The survey questions public servants about their views and contributions to democracy to gain a better understanding of what role they are playing in Canada’s system.
Keywords: public servants; democracy